Ultrasound-guided versus conventional injection for caudal block in children: A prospective randomized clinical study - Ahıskalıoğlu, Ali; Yayık, Ahmet Murat; Oral Ahıskalıoğlu, Elif; Ekinci, Mürsel; Gölboyu, Birzat Emre; Çelik, Erkan Cem; Alıcı, Hacı Ahmet; Oral, Akgün; Demirdöğen, Şaban O?uz (Elsevier Science Inc, 2018)
Study objective: The aim of this study was to compare the efficacies of ultrasound guided sacral hiatus injection and conventional sacral canal injection performed for caudal block in children. Design: Randomized controlled clinical trial. Setting: Operating rooms of university hospital of Erzurum, Turkey. Patients: One hundred-thirty four children, American Society of Anesthesiologists I-II, between the ages of 5 and 12, scheduled for elective phimosis and circumcision surgery. Interventions: Patients assigned to two groups for ultrasound guided caudal block (Group U, n = 68) or conventional caudal block (Group C, n = 66). Caudal solution was prepared as 0.125% levobupivacaine plus 10 mcg/kg morphine (total volume: 0.5 ml/kg), and was administered to both groups. Measurements: The block performing time, the block success rate, the number of needle puncture, the success at first puncture and the complications were recorded. Main results: The block performing time and the success rate of block were similar between Group U and Group C (109.96 +/- 49.73 s vs 103.17 +/- 45.12 s, and 97% vs 93%, respectively p > 0.05). The first puncture success rate was higher in Group U than in Group C (80% vs 63%, respectively p = 0.026). No significant difference was observed between the groups with regard to the number of needle punctures (p = 0.060). The rates of vascular puncture and subcutaneus bulging were higher in Group C than in Group U (8/66 vs 1/68, and 8/66 vs 0/68, respectively p < 0.05). Conclusions: Despite the limitations in central neuroaxial anesthesia we recommend the use of ultrasound since it reduces the complications and increases the success rate of first puncture in pediatric caudal injection.
WOS: 000423137700039
PubMed ID: 29161549
Keywords: Ultrasound Guided Caudal Injection; Sacral Hiatus; Sacral Canal; Pediatrics; Analgesia; Caudal Block